Determination of Discharge Flow in Unit Width for the Distinction of Nappe and Skimming Flow in Stepped Spillway Using Flow 3d (Case Study: Siah Bishe Dam) - Aydin Shishegaran; Mohammad Reza MohammadKhani; Mohammad Amin Tavakoli (پژوهش‌های زیرساخت‌های عمرانی, 2020)
One of the major challenges in dam engineering is the design of the discharge flow of the stepped spillway. The rate of energy dissipation in downstream currents is higher than that of skimming currents. To achieve this goal, the discharge and skimming slope of the spillway must be low, which makes it economically efficient and applicable. For this reason, in the design process of spillway discharge, flow is assumed to be skimming. In this study, after validation of the Flow-3D model, the discharge flow of the Siah Bishe spillway was simulated. For validation, the values of the flow-Ashle curve were evaluated, and the root means square error of 5.07 was obtained. According to the results of numerical simulation, the flow must be at least 17 m3/s for the discharge. As the flow rate increases, the flow will discharge and move into the state of transient flow, which will continue to flow with 37 cubic meters per second. Finally, for values of more than 60 cubic meters per second, the flow is definitely skimming.